Environmental Justice for Whom? Class, New Social Movements, and the Environment: A Case Study of Greenpeace Canada, 1971-2000 - Harter, John-Henry (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2004)
Abstract The 1970s saw an explosion of new social movement activism. From the break up of the New Left into single issue groups at the end of the 1960s came a multitude of groups representing the peace movement, environmental movement, student movement, women's movement, and gay liberation movement. This explosion of new social movement activism has been heralded as the age of new radical politics. Many theorists and activists saw, and still see, new social movements, and the issues, or identities they represent, as replacing the working class as an agent for progressive social change. This paper examines these claims through a case study of the quintessential new social movement, Greenpeace. This paper explores the history of Greenpeace Canada from 1971 to 2000 and its relationship to the working class. In order to understand the ideology behind Greenpeace, I investigate its structure, personnel, and actions. The case study illustrates important contradictions between new social movement theory and practice and how those contradictions affect the working class. In particular, Greenpeace's actions against the seal hunt, against forestry in British Columbia, and against its own workers in Toronto, demonstrate some of the historic obstacles to working out a common labour and environmental agenda.